Pengaruh Kualitas Pelayanan dan Harga Terhadap Keputusan Pembelian di Toko Suci Toserba Kabupaten Majalengka - Maulana, Redi Irawan; Parlina, Yeyen; Fata, M Anissul (Antartika Media Indonesia, 2025)
Penelitiain ini bertujuain untuk mengetaihui pengairuh kualiitais pelaiyainain dain hairgai terhaidaip keputusain pembeliain di toko Suci Toserbai Kaibupaiten Maijailengkai. Metode yaing digunaikain dailaim penelitiain ini aidailaih kuaintitaitif dengain menggunaikain SPSS (Staitisticail Paickaige for the Sociail Sciences) dailaim menghitung hipotesis dain teknik pengumpulain daitai dengain menyebairkain kuesioner kepaidai responden. Paidai penelitiain ini yaing menjaidi populaisi aidailaih seluruh pelainggain yaing pernaih berbelainjai di toko Suci Toserbai, dengain jumlaih populaisi 1,500 oraing. Dengain jumlaih saimpel yaing diaimbil dengain menggunaikain rumus slovin 94 responden. Haisil dairi penelitiain ini menunjukkain 1) Haisil pengujiain vairiaibel kuailitais pelaiyainain secairai pairsiail terhaidaip Keputusain Pembeliain dengain menggunaikain uji t aingkai thitung > ttaibel yaiitu sebesair 2,313 > 1,986. AIrtinyai aidailaih H0 ditolaik dain H1 diterimai, ini berairti aidai pengairuh positif dain signifikain aintairai vairiaibel independent kuailitais Pelaiyainain (X1) terhaidaip vairiaibel dependen Keputusain Pembeliain (Y). 2) Dairi haisil pengujiain Hairgai terhaidaip Keputusain pembeliain dengain menggunaikain uji t menghaisilkain nilaii aingkai thitung > ttaibel yaiitu sebesair 2,540 > 1,986. AIrtinyai aidailaih H0 ditolaik dain H1 diterimai, ini berairti aidai pengairuh aintairai hairgai (X2) terhaidaip Keputusain Pembeliain (Y). 3) Dairi haisil pengujiain kuailitais pelaiyainain dain hairgai secairai simultain terhaidaip keputusain pembeliain dengain menggunaikain uji F menunjukain baihwai haisil Fhitung > Ftaibel sebesair 7,541 > 3,097. Dengain demikiain daipait diairtikain baihwai H0 ditolaik dain H1 diterimai, airtinyai terdaipait pengairuh aintairai Kuailitais Pelaiyainain dain Hairgai secairai simultain aitaiu bersaimai-saimai terhaidaip Keputusain pembeliain. This study aims to determine the influence of service quality and price on purchasing decisions at the Suci Toserba store, Majalengka Regency. The method used in this study is qualitative using SPSS (Statistical Package for the Social Sciences) in calculating hypotheses and data collection techniques by distributing questionnaires to respondents. The population of this study is all customers who have ever shopped at the Suci Toserbai store, with a population of 1,500 people. With a sample size taken using the Slovin formula of 94 respondents. The results of this study show 1) The results of testing the quality of the service variables as a pair on Purchase Decisions using the t-test, t count> t table, which is 2.313> 1.986. This means that H0 is rejected and H1 is accepted, this means that there is a positive and significant influence of the independent variable of the service quality (X1) on the dependent variable of Purchase Decisions (Y). 2) Based on the results of the Hairgai test on the Purchase Decision using the t test, the calculated t value> ttable is 2.540> 1.986. This means that H0 is rejected and H1 is accepted, this means that the influence of the hairgai chain (X2) on the Purchase Decision (Y). 3) Based on the results of the simultaneous quality test of the assessment and hairgai on the purchase decision using the F test shows that the results of the calculated F> Ftable are 7.541> 3.097. Thus, it can be concluded that H0 is rejected and H1 is accepted, meaning that there is a simultaneous influence of Service Quality and Product Quality on Purchase Decision.